Assets Development of Video History Learning Based Animated 2.5D for Students SMPN 7 Depok - Yuly, Ade Rahma; Izzatii, Ulfah Nur (MULTINETICS, 2018)
"The history lesson is boring" is an assumption often raised by school students. Most history teachers still use lecture methods in class while there are many other methods that can be used to convey historical material. Based on the survey results of 8th grade students of SMPN 7 Depok thought that learning history would be more fun if using video animation and students also need animation video as one of the means of learning. 2.5D animated video created based on history lesson material for 8th grade students namely chapters Changes of Indonesian society during the colonial era and the growth of national spirit sub chapters of the arrival of the western nation. Assets of characters and background images are based on course material, are made in 2D using the image tracing method. The test is done by visual analog scale method. The test results show that the assets made in the form of characters and background make it easier for students to understand the material in the video.